Visualisasi 3D Exterior Masjid Penyengat - maria, Maria; Apriliaca , Vinchica (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The Sultan Riau Grand Mosque, also known as the Penyengat Mosque, is an important landmark due to its historical architectural details and symbol of the grandeur of the Islamic kingdom in Riau-Lingga. The grand imam of the mosque stated that, although it can be used as a religious and historical tourist destination. Therefore, the author plans to create a 3D visualisation of the mosque's exterior by employing the multimedia development life cycle (MDLC) method and conducting qualitative analysis with experts to ensure that the visualisation closely resembles the original. The process of creating the 3D visualisation of the Penyengat Mosque focused on important parts, such as the dome, minarets, and distinctive mosque decorations. The results of the study based on qualitative analysis indicate that the 3D visualisation of the exterior of the Penyengat Mosque is an accurate representation of the original structure, including architectural details and realistic textures that reflect the original building, although there are minor differences in the floor area.